Beyond Compliance: The Strategic Role of Organizational Citizenship Behavior in Managing Workplace Conflicts within Faith-Based Educational Institutions - Wahyudin, Wahyudin; Riinawati, Riinawati; Fuad Rasyid, Muhammad Zakiyyul; Suriagiri, Suriagiri; Yaqin, Husnul (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
This study examines the role of Organisational Citizenship Behaviour (OCB) in resolving conflicts within an Islamic educational setting. Conflicts are an inevitable aspect of collective life; yet, their management reflects the maturity and solidarity of an organisation. The research aims to identify and describe how OCB contributes to effective conflict management in maintaining organisational harmony. Using a qualitative case study design, data were collected through purposive and snowball sampling, with observations, interviews, and document analysis. The data were analysed using an inductive conceptualisation approach to capture patterns emerging from participants’ experiences. The findings reveal that conflicts within the institution are generally situational and temporary, and do not escalate into latent disputes. The existence of organisational forums, a tradition of deliberation, and the strong leadership role of spiritual figures ensure that conflict management operates effectively. Furthermore, collective solidarity is reinforced through cooperative problem-solving and mutual agreements. OCB—manifested through sincerity, humility, loyalty, and faith in spiritual rewards—serves as social capital in preserving social equilibrium. The integration of spirituality-based OCB and deliberation-oriented conflict resolution fosters a resilient and adaptive organisational culture. These findings suggest that cultivating spirituality-driven OCB can transform conflict from a disruptive force into a constructive process of social learning and institutional strengthening.